The Role of Bank Credit, Financial Management, and Access to Capital in Enhancing MSME Sustainability - Wimpi Srihandoko; Hendra Setiawan; Soei Khim (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting economic growth and employment; however, maintaining business sustainability remains a major challenge, particularly in relation to financing and financial management. This study aims to examine the effects of bank credit, financial management, and access to capital on MSME sustainability. A quantitative approach with a cross-sectional design was employed, and data were collected through a structured questionnaire administered to 120 MSME owners in Bogor City, West Java, selected using purposive sampling. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The results indicate that bank credit, financial management, and access to capital all have positive and significant effects on MSME sustainability. Among these factors, financial management demonstrates the strongest influence, highlighting the critical role of internal financial capability in enhancing business sustainability. The coefficient of determination shows that the proposed model explains a substantial proportion of the variance in MSME sustainability. These findings suggest that access to external financing alone is insufficient to ensure long-term sustainability unless supported by effective financial management practices. This study contributes to the MSME sustainability literature by integrating external financing and internal financial capability within a single empirical model and provides practical insights for MSME owners, financial institutions, and policymakers in designing integrated strategies to strengthen sustainable MSME development. Keywords: Bank Credit; Financial Management; Access to Capital; MSME Sustainability